Share issues and repurchases related to equity market timing on the JSE - Potgieter, Fahmida (My University, 2016)
Information asymmetry creates a gap between management’s perception of the firm’s value and the market value of the firm. It is thought that management engage in information signalling activities in order to close the gap created by information asymmetry. There is a need to understand why management engage in their chosen transactions as this will provide investors with insight into market activities, as well as allow for more accurate investment strategies. While research is available on the market’s reactions to signalling events, the problem is whether management’s intentions have been correctly interpreted by the market. The starting point to gaining this understanding is to ask the question: What signals do management send when they issue and repurchase shares? This study attempts to answer this question by investigating whether companies listed on the Johannesburg Stock Exchange (JSE) issue shares because management perceive their market values to be overvalued and repurchase shares because their market values are undervalued. For the period 1 January 2003 to 31 December 2012, a total of 295 share issue announcements are considered for 102 companies; and a total of 183 share repurchase announcements are considered for 83 companies. The results of this study reveal that managerial equity market timing may exist in the presence of excess returns, where management are better able to predict returns in advance than the market. However, there is also evidence suggesting share repurchases are made to return excess cash to shareholders and issues and repurchases decisions are linked to capital structure planning. The fact that there are other potential reasons for share issues and repurchases, means that the market must be able to determine what the real intentions of management are when shares are issued and repurchased; and hence determine whether their intentions suggest equity market mispricing.
A 50% dissertation presented in partial fulfilment of the requirements for the degree of Master of Commerce at the University of Witwatersrand.
Keywords: Stocks; Prices; Johannesburg Stock Exchange; Repurchase; Shares